Studi Kelayakan Penerapan Panel Surya pada PJU Menggunakan Metode Life Cycle Cost dan Payback Period (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to analyze the feasibility of implementing Solar-Powered Street Lighting (PJUTS) as an alternative lighting solution in Campus C of UNINDRA PGRI. The background of this research is driven by the high operational electricity costs of the existing conventional street lighting system and the need to transition toward clean energy. The analysis methods include a technical comparison of off-grid systems, an economic evaluation based on cost savings, and an assessment of environmental impacts. The technical analysis indicates that PJUTS is highly feasible due to its ability to operate independently without reliance on the national electricity grid, thereby ensuring lighting continuity during power outages. From an economic perspective, although the initial investment (CAPEX) is higher than that of conventional street lighting, the project is considered feasible as it eliminates monthly electricity bills permanently, resulting in long-term budget efficiency and financial benefits. The Payback Period analysis shows that the initial investment can be recovered through cumulative operational cost savings. Environmentally, the implementation of PJUTS significantly contributes to carbon emission reduction and supports the Green Campus vision through the utilization of renewable energy. Overall, the transformation of the existing street lighting system into PJUTS represents a strategic and feasible initiative that fulfills effectiveness, efficiency, and sustainability criteria.